Corruption, financial development and capital structure: evidence from China. Issue 3 (21st August 2017) - Wei, Feng; Kong, Yu
Abstract : Purpose: This paper takes listed companies in the Shanghai and Shenzhen stock markets from 1998 to 2013 as a research sample, investigating the role played by corruption and financial development, along with the interactions between the two, in determining the factors of a company's capital structure in China's legal environment. The paper aims to discuss these issues. Design/methodology/approach: Using data of listed companies and the regional level of China during 1998-2013 and the STATA process (xtabond2 command) developed byRoodman (2006) to implement the two-step GMM estimation, empirically investigate the effect of interactions between corruption and financial development on a company's capital structure in Chinese legal environment. Findings: After both controlling for China's legal environment, a company's internal factors, and industry factors and considering endogeneity problems, the results show that corruption and financial development have significant positive influences on a company's bank loans. However, when investigating the interactions between corruption and financial development, the authors find that financial development does not increase a company's bank loans in areas with a higher level of corruption. However, corruption and financial development have insignificant influences on a company's long-term bank loans. Research limitations/implications: The findings in this study suggest that a company's capital structure was affected not only by the company's internal factors and industry factors, but also by the company's external factors, and the interactions between these factors. Practical implications: To improve the financing circumstances of company credit, the next point of reform should be to improve their procedures for administrative examination and approval of bank creditors and strengthen the punishment and prevention of credit and judicial corruption to weaken the negative effects of corruption on firms' capital structure decisions. Originality/value: This study uses only Chinese listed companies, and considers the influence of the interaction of corruption and financial development on a company's capital structure decisions.